2021
DOI: 10.1016/j.omtm.2021.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Cell therapy with hiPSC-derived RPE cells and RPCs prevents visual function loss in a rat model of retinal degeneration

Abstract: Photoreceptor loss is the principal cause of blindness in retinal degenerative diseases (RDDs). Whereas some therapies exist for early stages of RDDs, no effective treatment is currently available for later stages, and once photoreceptors are lost, the only option to rescue vision is cell transplantation. With the use of the Royal College of Surgeons (RCS) rat model of retinal degeneration, we sought to determine whether combined transplantation of human-induced pluripotent stem cell (hiPSC)-derived retinal pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 56 publications
1
21
0
Order By: Relevance
“…In this regard, we first assessed the cell integrity and purity of our hiPSC-RPE cultures to exclude undifferentiated cells using a protocol of cell sorting and purification by extensive culture and passaging. Upon transplantation, there was no evidence of neoplastic or teratoma structures or any other adverse event in any of the transplanted porcine eyes studied, in accordance with other studies in different animal models and in humans [ 12 , 58 , 59 , 64 ]. Furthermore, there was no evidence of endophthalmitis, retinal edema, uveitis, epiretinal membrane, proliferative vitreoretinopathy, encapsulation, or retinal rupture in the immunosuppressed animals.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this regard, we first assessed the cell integrity and purity of our hiPSC-RPE cultures to exclude undifferentiated cells using a protocol of cell sorting and purification by extensive culture and passaging. Upon transplantation, there was no evidence of neoplastic or teratoma structures or any other adverse event in any of the transplanted porcine eyes studied, in accordance with other studies in different animal models and in humans [ 12 , 58 , 59 , 64 ]. Furthermore, there was no evidence of endophthalmitis, retinal edema, uveitis, epiretinal membrane, proliferative vitreoretinopathy, encapsulation, or retinal rupture in the immunosuppressed animals.…”
Section: Discussionsupporting
confidence: 89%
“…The RPE cells generated from hiPSC in this study have previously been shown to have specific RPE functions in vitro, such as phagocytosis of photoreceptor outer segments, ion transport, polarized factor secretion, membrane potential, and gene expression, similar to their native counterparts [ 56 , 57 ]. Extending our previous work on differentiation of hESC and hiPSC to RPE cells [ 58 , 59 , 60 ], here, we have further characterized differentiated RPE cells from human cord blood-derived iPSC, and shown that they exhibit cell properties, in vitro functions, and gene expression similar to native RPE cells. Our RPE confluent cultures expressed apical tight junctions and reached a TEER of >200 Ω·cm 2 , which is similar to that seen in vivo [ 56 ], suggesting a strong polarization and good tight junction integrity, important for their barrier function.…”
Section: Discussionmentioning
confidence: 72%
“…In addition to transplanting stem cells and their derivatives, future therapeutic options can include cotransplantation of two or more types of cells to achieve a better clinical benefit. 16,60 Further, stem cells can be modified to overexpress retinal regenerative factors, 31,32,61 and utilization of scaffolds to culture and transplant the stem cells and their derivations might improve their clinical benefits. 62,63 However, there is a lack of consensus on the route of administration, method of evaluation of outcome, source of stem cells, and the long-term effect of stem cell transplantations.…”
Section: Discussionmentioning
confidence: 99%
“…15 Interestingly, co-transplantation of RPCs and RPE cells derived from iPSCs was superior to transplanting individual cell types, it resulted in better visual response and preservation of ONL in a rat model of retinal degeneration. 16 Further, in an animal model of RP, subretinally transplanted iPSC-derived CRX-expressing photoreceptor precursors engrafted at the inner nuclear layer (INL). The transplanted cells expressed the pan cone marker, Arrestin 3, indicating further maturation.…”
Section: Preclinical Studies With Stem Cells Escsmentioning
confidence: 99%
See 1 more Smart Citation